High performance, flexible, and thermally stable all-solid-state organic electrochemical transistor based on thermoplastic polyurethane ion gel - Hou, Kunqi (2023)
Organic electrochemical transistors (OECTs) are a generation of transistors with high transconductance, where the whole volume of the semiconducting channel is involved in the electrochemical doping process. However, the use of liquid electrolytes limits the application of OECTs, and the doping process is also complicated due to the presence of water in the electrolyte. In this study, thermoplastic polyurethane (TPU)-based solid electrolyte was used in OECTs for the first time. Three types of ionic liquids were blended with a TPU polymer matrix as a solid electrolyte and investigated on the OECTs based on three kinds of p-type conjugated semiconductors. An in situ spectrochemistry study was further carried out to confirm the doping/dedoping process of these conjugated semiconductors by the TPU-based solid electrolyte. The robustness and high stability of the fabricated solid-state OECTs (SSOECTs) were demonstrated through continuously applied bias, long time operation under ambient conditions, and varying temperatures (−50 to 120 °C). Highly flexible SSOECTs were also obtained on a polyethylene terephthalate (PET) substrate, which showed negligible fluctuation in on/off-current (Ion/Ioff) after 1000 cycles of bending. Based on these highperforming SSOECTs, inverter circuits were fabricated in both unipolar and complementary configurations, where n-type and p-type OECT-based complementary inverters showed a higher gain (46) compared with that of the unipolar design.